Ectrópio palpebral: Características e relação com alterações óculo-palpebrais - Dos Reis Veloso, Carlos Eduardo [UNESP]; Schellini, Silvana Artioli [UNESP]; Padovani, Carlos Roberto [UNESP]; Padovani, Carlos Roberto [UNESP] (My University, 2006)
Objective: To evaluate the gender and the characteristics of the ectropion carriers in our region. Methods: A retrospective study was done evolving 112 ectropion carriers. The sex, race, eyelashes alterations (trichiasis and distichiasis), anterior and posterior blepharitis, conjunctival redness, íris color and pterygium presence were evaluated. Gender data were correlated to ectropion classification (involutional, cicatricial, mechanic or paralytic) and submitted to statiscal analysis. Results: The eyelid ectropion occurred more between 71 and 80 years old.The involutional ectropion was the most frequently observed (66,07%), followed by the cicatricial, mechanic, associated types and paralytic. The majority of the patients were male (70,53%), with White skin. Trichiasis (21,42%) and distichiasis (4,46%) were associated to the ectropion eyelid and mainly in the involutional ectropion carriers. Half of the sample had blepharitis and the majority of the patients had red eye (60%) and brown iris (63,39%). Perygium was absent in the majority of the patients. Conclusion: The involutional ectropium is the most frequently observed in our region, mainly in elderly, male, White skin, brown iris and associated to trichiasis, blepharitis and red eyes.
Palpebral ectropion: Characteristics and related eyelid and ocular alterations
Keywords: Ectropion/epidemiology; Eyelid diseases